PENGARUH LATIHAN INTERVAL TRAINING DAN LARI FARTLEK TERHADAP DENYUT NADI PADA MAHASISWA - Ratno Susanto (Jayabama: Jurnal Peminat Olahraga, 2024)
This researcher aims to find out how much endurance increases after 18 interval training exercises and fartlek running in class B male students at Insan Budi Utomo University. The method used in this research is quantitative, namely the research results are presented in the form of descriptions using numbers. Meanwhile, the data collected is quantitative, which is explained using statistical calculations. To calculate further, use simple analysis techniques that describe the state of a phenomenon. The population and sample were 36 class B male students at Insan Budi Utomo University. Based on the research results of the instruments studied using simple statistics that look for the mean, it can be explained that the interval training and fartlek training instruments have quite an effect on the endurance of Class B male students at Insan Budi Utomo University after taking the 2,400 meter final test, because it can be seen from the final score. shows the pulse rate before interval training and fartlek running (114-158), the pulse rate after interval training exercise (110-115) in this way it can be concluded that interval training and fartlek running really help improve endurance conditions in male B students at Insan Budi University Utomo